Assessing the Impact of ESG Standards and Regulations on the Audit Process - Andreea Larisa Olteanu (Burca); Alina Elena Ionascu; Bianca Paula Ciumacencu (Ovidius University Annals: Economic Sciences Series)
The purpose of this paper is to assess the impact of ESG (Environmental, Social, and Governance) standards and regulations on the audit process. The growing significance of sustainability in business, driven by regulatory pressure, stakeholder expectations, and the demand for transparency, has transformed the audit landscape. Auditors now play a key role in verifying ESG disclosures, ensuring compliance with frameworks like the EU Taxonomy, SFDR, and TCFD recommendations, and safeguarding against risks such as greenwashing. As businesses integrate ESG criteria into their strategies, auditors must adapt methodologies to evaluate non-financial, often subjective, data. Independent assurance on ESG reporting is increasingly vital to enhance credibility, meet regulatory requirements, and build stakeholder trust. This evolution highlights the critical role of auditors in promoting transparency, accountability, and long-term business resilience in an environment where ESG factors are reshaping corporate practices globally.